2012
DOI: 10.1108/08876041211237578
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing relationship development in franchise partnerships

Abstract: PurposeThis paper aims to identify and evaluate the factors which influence relationship development between franchisors and franchisees in international service franchise partnerships.Design/methodology/approachCase studies of two international hotel firms were the focus of the enquiry. Interviews and document analysis were used as the data collection techniques.FindingsFindings demonstrate that role performance, asset specificity and cultural sensitivity influence relationship development in franchise partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 106 publications
1
55
0
Order By: Relevance
“…Research has shown that the ability of a firm to break down cultural barriers and establish close business relationships with partners is a major factor for success in international business marketing (e.g., Terawatanavong & Quazi, 2006). Unless exporters are sensitive to the cultural aspects of buyer-seller relationships, it is very difficult to build long-term high-quality relationships (Altinay & Brookes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the ability of a firm to break down cultural barriers and establish close business relationships with partners is a major factor for success in international business marketing (e.g., Terawatanavong & Quazi, 2006). Unless exporters are sensitive to the cultural aspects of buyer-seller relationships, it is very difficult to build long-term high-quality relationships (Altinay & Brookes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a franchise system as an interfirm relationship, mutual trust between the franchisor and franchisee is important for them in performing their own tasks (Victoria Bordonaba-Juste and Polo-Redondo, 2008). Trust is an important factor in the franchising relationship Frazer, 2006, Watson andJohnson, 2010), and encourages both parties to maintain and develop the relationship (Victoria Bordonaba-Juste and PoloRedondo, 2008), work successfully (Eser, 2012) and achieve mutual profitability (Davies et al, 2011 , Altinay andBrookes, 2012).…”
Section: Trustmentioning
confidence: 99%
“…(Justis & Judd, 2002;Kaufmann & Stanworth, 1995;Lim & Frazer, 2004;Williamson, 1995;among others). Likewise, a franchisee receiving satisfactory support from the franchisor partner develops confidence in the franchisor's capabilities (Altinay & Brookes, 2012;Flint-Hartle & de Bruin, 2011;Hing, 1995). Therefore, the relationship between the franchisor and franchisee is of vital importance for the development and success of a franchise.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers recognize the need to create a collaborative and cooperative atmosphere to handle tensions (Altinay & Brookes, 2012). Franchisors should identify areas or factors franchisees are dissatisfied with, and areas they are not to deal with these tensions.…”
Section: Introductionmentioning
confidence: 99%